Osteoclast Activation and Inflammatory Bone Diseases: Focusing on Receptors in Osteoclasts - Zhao W; Li J; Su T; Wang C; Fu Y; Li C; Hua P; Liang X; Zhu Y; Cui H (Journal of Inflammation Research)
Weijie Zhao,1,* Ji Li,1,2,* Tian Su,3,4 Chuanling Wang,5 Yonghua Fu,6 Changjia Li,1 Pengbing Hua,1 Xuelong Liang,7 Yongjun Zhu,8 Hongwang Cui1 1Key Laboratory of Emergency and Trauma of Ministry of Education, Department of Emergency Surgery, Key Laboratory of Hainan Trauma and Disaster Rescue, The First Affiliated Hospital, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 2The Second Affiliated Hospital of Hainan Medical University, Haikou, Hainan, People’s Republic of China; 3Key Laboratory of Emergency and Trauma, Ministry of Education, Key Laboratory of Haikou Trauma, Key Laboratory of Hainan Trauma and Disaster Rescue, The First Affiliated Hospital of Hainan Medical University, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 4Engineering Research Center for Hainan Bio-Smart Materials and Bio-Medical Devices, Key Laboratory of Hainan Functional Materials and Molecular Imaging, College of Emergency and Trauma, College of Pharmacy, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 5Department of Internal Medicine of Donghu, The Second Affiliated Hospital of Hainan Medical University, Haikou, Hainan, People’s Republic of China; 6Department of Hand and Foot Microsurgery, The Second Affiliated Hospital of Hainan Medical University, Haikou, Hainan, People’s Republic of China; 7The First School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, People’s Republic of China; 8Department of Nephrology, The First Affiliated Hospital, Hainan Medical University, Haikou, Hainan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongwang Cui, Key Laboratory of Emergency and Trauma of Ministry of Education, Department of Emergency Surgery, Key Laboratory of Hainan Trauma and Disaster Rescue, The First Affiliated Hospital, Hainan Medical University, Haikou, Hainan, People’s Republic of China, Email cqchw2013@sina.com Yongjun Zhu, Department of Nephrology, The First Affiliated Hospital, Hainan Medical University, Haikou, Hainan, People’s Republic of China, Email zzjjyybox@163.comAbstract: Bone homeostasis depends on the balance between osteoblast-mediated bone formation and osteoclast-mediated bone resorption. An increasing number of studies have revealed that under inflammatory conditions, osteoclast overactivation is responsible for bone loss in relevant bone diseases. Multiple signaling pathways such as receptor activator of nuclear factor-kappa B ligand (RANKL) signaling are involved in osteoclast activation. These signaling pathways rely on various receptors expressed on the surface of osteoclast progenitor cells (OPCs) or osteoclasts, which are activated by their corresponding ligands and subsequently trigger intracellular signaling. Targeting of these receptors may exert an inhibitory effect on osteoclast activation and inflammatory bone diseases. In this review, we discuss osteoclast activation and receptors involved in this process. The role of these receptors in relevant bone diseases has also been discussed.Keywords: osteoclast, receptor, inflammation, bone loss, osteoporosis, arthritis